Co-Citation Analysis of Pedagogical Leadership Research: A Systematic Literature Review (1998-2023) - Wildansyah Lubis; Rosmala Dewi; Zuraida Lubis; Muhammad Bukhori Dalimunthe; Gaffar Hafiz Sagala (FKIP Universitas Lampung, 2024)
Co-Citation Analysis of Pedagogical Leadership Research: A Systematic Literature Review (1998-2023). Objectives: This study aims to (1) analyze the development of pedagogical leadership research using bibliographical and co-citation analysis and (2) formulate future research directions related to pedagogical leadership. Methods: This study uses bibliometric and co-citation analysis techniques to understand phenomena based on published research. We collected articles from the Scopus repository as it is a significant and credible academic article database. This study collected 126 articles published in English-language journals from 1998 to 2023. Findings: The results show the demographics of the articles collected, publication productivity based on country, and five clusters, which discuss in detail the research development and the direction of future research issues related to pedagogical leadership. Conclusion: Implicatively, this literature review offers several future research agendas related to pedagogical leadership, which are described in the discussion section. This research agenda can be followed up by scholars and education stakeholders who have the potential to improve the quality of learning and teacher professionalism. Keywords: instructional leadership, pedagogic, bibliometric.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202464